Maternal fish oil supplementation improves metabolic and inflammatory markers in mice overfed during the postnatal period - Lopes, Isabela Queiroz Perígolo; Monteiro, Brenda Loise; Ferreira, Adaliene Versiani Matos; de Moura, Rodrigo Ferreira; de Sales Guilarducci, Janina; Leão, Estéfany Ribeiro; do Carmo Rodrigues Virote, Bárbara; Konig, Isaac; Murgas, Luis David Solis; de Castro, Isabela Coelho; Pimenta, Laura Cristina Jardim Porto (Frontiers in Nutrition, 2025)
BackgroundEarly-life nutrition, especially during gestation and lactation, plays a key role in metabolic programming and can influence the risk of obesity and related conditions in adulthood. This study investigated whether supplementation with maternal fish oil—rich in omega-3 polyunsaturated fatty acids—could prevent metabolic and inflammatory changes induced by postnatal overfeeding.MethodsFemale mice received fish oil (1 g/kg by oral gavage) during mating, pregnancy, and lactation. The animals were allocated into three groups: control (C), postnatal overfeeding (PO), and postnatal overfeeding + fish oil (POFO). Neonatal overfeeding was induced by reducing litter size, and only male offspring were analyzed. In adulthood, body weight, glucose tolerance, lipid profile, serum adipokines, adipose tissue cytokines, and hepatic oxidative stress markers were evaluated.ResultsMaternal fish oil supplementation reduced early weight gain and lowered fasting glucose, total cholesterol, and low-density lipoprotein (LDL) levels, while increasing high-density lipoprotein (HDL) levels in overfed offspring. It also decreased serum leptin, resistin, and chemerin levels and reduced hepatic lipid peroxidation, thereby restoring catalase activity. No differences were observed in hepatic triglycerides or superoxide dismutase activity.ConclusionMaternal fish oil supplementation during critical developmental windows attenuated the metabolic, inflammatory, and oxidative stress alterations induced by postnatal overfeeding in male mice.